Index extensor digitorum communis tendon entrapment in a growth plate injury of distal radius. (August 2019) - Furuya, Hiroyuki; Naito, Kiyohito; Sugiyama, Yoichi; Goto, Kenji; Nagura, Nana; Shimamura, Yoshio; Iwase, Yoshiyuki; Kaneko, Kazuo
Abstract: Background: We report a rare case in which an epiphyseal injury of the distal radius caused entrapment and rupture of the index extensor digitorum communis tendon during conservative treatment. Case presentation: A 16-year-old girl suffered epiphyseal injury of the right distal radius with palmar displacement during playing judo. Closed reduction and application of a short arm cast were performed. 4 weeks after injury, movement of her index finger was limited. Extensor tendons adhesion at the fracture site was suspected. It was found that the index extensor digitorum communis tendon had become trapped and ruptured at the site of epiphyseal injury, then reconstruction was done by tendon transfer. At 12 months after surgery, the patient had resumed judo at the same level as before the injury. Conclusions: The present case suggested that there is a risk of extensor tendon entrapment associated with closed reduction.